Ordem cultural e desenvolvimento local participativo: estrutura para a prática do terapeuta ocupacional. - Lopes Correia, Ricardo; Santiago da Rocha, Camila (Cadernos de Terapia Ocupacional da UFSCar, 2016)
The Cultural Order is understood as the expression of a game of interdependencies determinations between local and global social groups, pairs identified by productions, values and behavior that consciously guide the life projects and the expansion of a collective freedom. Based on a Social Science research and with theoretical mark of Nobert Elias and Amartya Sen, this article aims to present a theoretical-practice structure of the approach in participatory local development- PLD to the occupational therapist surround by the construction of collective life projects, in order to operationalize in the practice of the community question, understood as the strengths that singularize the participation. We discuss the use of the PLD approach to the occupational therapist in a flexible structure, aiming to guarantee its domain, the Human Occupation, and the set of interventions, technologies, sustained in the management of the activities of daily living. The approach in participatory local development presents itself as an important structural outline to the community actions, and it is the occupational therapist role to be an articulator of the Local Cultural Order dimensions, to deal with the target population their work processes of continuity in collective life projects and expansion of freedom.